Disney animation : the illusion of life. - Thomas, Frank, ....-; Johnston, Ollie, ....- (New York : Abbeville, 1981)
An out-of-print collectors item since 1986, the definitive account of the development of Disney animation explains what made Disneys style unique and features original sketches and drawings revealing the origins of Mickey and the rest. National adromo.
Keywords: Animatie; Disney; Tekenen